Patient‐reported outcomes with subcutaneous immunoglobulin in chronic inflammatory demyelinating polyneuropathy: the PATH study. (23rd September 2019) - Hartung, H.‐P.; Mallick, R.; Bril, V.; Lewis, R. A.; Sobue, G.; Lawo, J.‐P.; Mielke, O.; Durn, B. L.; Cornblath, D. R.; Merkies, I. S. J.; van Schaik, I. N.
Abstract : Background and purpose: Chronic inflammatory demyelinating polyneuropathy (CIDP) causes weakness which adversely impacts function and quality of life (QOL). CIDP often requires long‐term management with intravenous or subcutaneous immunoglobulin. The Polyneuropathy and Treatment with Hizentra® (PATH) study showed that subcutaneous immunoglobulin (SCIG) was efficacious in CIDP maintenance. Here, patient‐reported outcomes in patients on SCIG are assessed. Methods: Subjects stabilized on intravenous immunoglobulin were randomly allocated to receive weekly 0.2 or 0.4 g/kg bodyweight of 20% SCIG (IgPro20) or placebo. Overall QOL/health status was assessed using the EuroQoL 5‐Dimension (EQ‐5D) health profile and visual analog scale, treatment satisfaction was assessed with the Treatment Satisfaction Questionnaire for Medicine (TSQM) and work‐related impact was assessed with the Work Productivity and Activity Impairment Questionnaire for General Health (WPAI‐GH). The EQ‐5D health profile was assessed in terms of the percentage of subjects maintained or improved at week 25 of SCIG therapy on each of the EQ‐5D domains versus baseline after intravenous immunoglobulin stabilization. TSQM and WPAI‐GH were assessed by median score changes from baseline to week 25. Results: In total, 172 subjects were randomized to placebo ( n = 57), 0.2 g/kg IgPro20 ( n = 57) and 0.4 g/kg IgPro20 ( n = 58). Significantly higher proportions of IgPro20‐treated subjects improved/maintained their health status on the EQ‐5D usual activities dimension, and in additional dimensions (mobility and pain/discomfort) in sensitivity analyses. TSQM and WPAI‐GH scores were more stable with IgPro20 treatment compared with placebo. Conclusions: IgPro20 maintained or improved QOL in most subjects with CIDP, consistent with the PATH study findings that both IgPro20 doses were efficacious in maintaining CIDP.